Anticoagulant-induced oral bleeding - Costa, Victor; Kaminagakura, Estela (Brazilian Dental Science, 2017)
Warfarin is an anticoagulant used to prevent thrombosis, cardiac arrhythmias, atrial fibrillation, and recurrence of pulmonary embolism. A 69-year-old male patient reported episodes of four heart attacks, stroke, pulmonary emphysema, varicose veins, thyroid dysfunction, and a history of angioplasty. They use daily dose of 5 mg. Intraoral clinical examination revealed a bleeding nodular lesion of purple color with irregular borders and a smooth surface. The prothrombin time was 68.9 seconds, activity was 10%, and the international normalized ratio (INR) was 8.26. Based on these results, the patient received a single dose of 2.5 mg vitamin K via subcutaneous route. The final diagnosis was oral anticoagulant-induced lesions. Clinicians should be familiar with the side effects of anticoagulants, which are rare in the oral cavity, but can be life-threatening if diagnosed late or inaccurately, especially in older patients that often use many drugs. Keywords Anticoagulant; Hemorrhage; Warfarin; Mouth.